Pharmacogenomic paradigm shift: Circulating microRNAs as a missed mechanism in carbamazepine-induced resistant hypertension - Bozoglan, Merve Yilmaz (Elsevier, 2026)
Carbamazepine (CBZ) is associated with rare, severe hypertension cases that remain characteristically refractory to conventional antihypertensive therapy, resolving only upon drug cessation. It is hypothesized that CBZ-induced refractory hypertension is mediated by the dysregulation of specific circulating microRNAs that target core vascular tone and renin-angiotensin system components. The rarity of this adverse drug reaction and the difficulty of acquiring clinical biosamples hinder validation through classical trials. Therefore, a transition to controlled in vivo and in vitro experimental designs is essential to validate this novel mechanistic pathway, ultimately advancing pharmacovigilance and rational drug use.
Keywords: Adverse Drug Reaction; Carbamazepine; Hypertension; Microrna